Ołów i władza: plomby Rurykowiczów i Piastów w Europie środkowo-wschodniej - MUSIN, ALEKSANDR (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2022)
The article considers the economic and political use of small lead seals (tag seals) to validate different kinds of social relations in early medieval Poland and Rus’. Originated in Antiquity, the practice of sealing peaked in Byzantium from where it spread to Early Rus’. This is reflected, for example, in the use in late 11th-late 14th centuries of small lead seals referred to as the “Drohiczyn type”. In this paper I put forward an opinion that not all the early medieval small lead seals should be attributed to “coinless economy”. A study of the corpus of small lead seals from Drohiczyn and Czermno, and finds from Mazovia, has identified a group with iconography identical to the Polish Hohlpfennig, suggesting they were commercial-customs small lead seals used by the Piast dynasty, contemporary with the bracteates introduced in the first half/mid-13th-early 14th centuries. The extraordinary number of small lead seals found in Drohiczyn possibly reflects the outstanding position of the town in the Eastern and Central European relationships as well as a short-term relocation of trade routes leading north, caused by the military conflicts of the 1240-1280s in the upper course of the Western Bug. The practice of sealing could have been introduced by Conrad of Mazovia to Poland from Early Rus’. Subsequently, the small Polish lead seals might have contributed to the emergence of lead cloth seals in Western Europe as part of a cultural transfer.